Professional consciousness and pride facilitate evidence‐based practice-The meaning of participating in a journal club based on clinical practice reflection - Malene Beck; Charlotte Simonÿ; Heidi Bergenholtz; Susanne Hwiid Klausen (Wiley, 2020)
Abstract Aim An evidence‐based approach should permeate clinical nursing practice, but many nurses lack confidence in applying relevant research evidence to clinical practice. Journal club participation can increase evidence‐based practice knowledge and skills while facilitating positive attitudes among participants. Thus, the aim was to describe the experience of nurses in participating in a journal club based on a curriculum derived from their practice narratives. Design The study employed a phenomenological hermeneutical approach. Qualitative data from six focus groups with 19 nurses were interpreted in a three‐step process influenced by the French philosopher Paul Ricoeur. Methods Influenced by narrative pedagogy and critical reflection through problem‐based learning, a journal club named Reflexivity was facilitated in three 2‐hourly workshops over eight weeks and evaluated together with nurses across three clinical departments. Results Three themes are identified: (a) professional reflections are an oppressed aspect of daily nursing; (b) revealing nursing from the hidden; and (c) emerging consciousness in nursing. The study concludes that Reflexivity has the potential to integrate evidence‐based knowledge and increase professional consciousness by reflection on clinical questions in an evidence‐based context. Fundamental issues of nursing care are raised, and feelings of essential pride in nursing are facilitated. Thus, evidence‐based nursing practice is embarked through a journal club based on the participant's narratives.